P138 Identifying the Prevalence of Recreational Drug Use in Men Who Have Sex With Men Attending Sexual Health Clinics in Greater Manchester. (30th June 2016) - Tomkins, Andrew; Ahmad, Sameena; Cannon, Luke; Higgins, Stephen P; Kilner, Merav; Kolyva, Anastasia; Ward, Chris; Vivancos, Roberto
Abstract : Background/introduction: Recreational drug use has been reported to be disproportionately higher in men who have sex with men (MSM) when compared to their heterosexual counterparts. There are indications that increased recreational drug use may lead to risky sexual behaviour. Patterns of recreational drug use are subject to spatial and temporal variations and as such, regular assessment of these changes is essential in understanding service user behaviour. Aim(s)/objectives: To identify commonly used recreational drugs, routes of administration and frequency of use for MSM service users attending sexual health clinics in Greater Manchester. Methods: A retrospective case note review was conducted using a random, powered sample of MSM attending three sexual health clinics across Greater Manchester during 2014. Details of risky sexual practices, sexually transmitted infection diagnoses and number of sexual partners were also recorded. Results: 357 case notes were reviewed from across three sites. In total, 18% of service users reported recreational drug use. The most commonly reported substances were cannabis (7%) and cocaine (6%). 3.7% of service users reported using at least one of the three main drugs typically associated with chemsex. Discussion/conclusion: Our study identified that substance misuse is common in MSM attending sexual health clinics in Greater Manchester. It highlights the need for the robust collection of data during consultation in order to better understand service user requirements.